Energia líquida de dietas submetidas a diferentes processamentos e suplementações enzimáticas para suínos em crescimento - Andressa da Silva Fomigoni (2016)
Aiming to evaluate the effect of different particle sizes and physical form of the feed and the effect of different enzymes supplementation on digestibility coefficients of dry matter (CDMS), crude protein (CDPB), gross energy (CDEB), digestible energy values (ED), metabolizable (EM), ratio metabolizable energy:digestible energy (EM:ED), heat production (PC), calorie incremente (IC) and net energy (EL) two experiments were carried out. Were used 16 pigs in experiment I and 20 pigs in experiment II, castrated males of comercial lineage with average initial weight of 25 kg. The experimental design was completely randomized, on what, being the experiment I composed of four treatments and four replicates and experiment II for four treatments and five replicates, and one animal per experimental unit. In experiment I, treatments consisted of two mashs diets, with DGM of 614 m and 888 m and pelleted diets with different pellet sizes, in which, in pellet thin DGM was 614 m, and the coarse pellet DGM was 888 m, and the experiment II, feed containing different enzymes (control diet, amylase + celulase + protease, -mananase and -galactosidase). The diets used in both experiments were isoenergetic and isoproteic, formulated to meet the nutritional requirements of animals in the growth phase. The analyzed variables were submitted to analysis of variance and the data of the experiment I were compared by SNK test and experiment II by Dunnet, the 5% probability. No differences were found (P0,05) on the digestibility and energy values of both experiments. It is concluded that the enzyme supplementation and processing does not influence the digestibility and energy values of the diets for growing pigs.